2007
DOI: 10.1021/ol0631152
|View full text |Cite
|
Sign up to set email alerts
|

Click Chemistry in CuI-zeolites:  The Huisgen [3 + 2]-Cycloaddition

Abstract: [reaction: see text] CuI-exchanged solids based on zeolite materials were investigated for the first time as catalysts in organic synthesis. The catalytic potential of these materials was evaluated in the Huisgen [3 + 2]-cycloaddition. Five CuI-exchanged zeolites were examined and CuI-USY proved to be a novel and efficient heterogeneous ligand-free catalyst for this "click chemistry"-type transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 249 publications
(109 citation statements)
references
References 20 publications
6
101
1
1
Order By: Relevance
“…Moreover, all examined solvents including protic solvents proved suitable for this reaction, but toluene was the most effective and the cleanest at r. t. (Fig. 3) [20].…”
Section: Unauthenticatedmentioning
confidence: 95%
“…Moreover, all examined solvents including protic solvents proved suitable for this reaction, but toluene was the most effective and the cleanest at r. t. (Fig. 3) [20].…”
Section: Unauthenticatedmentioning
confidence: 95%
“…All triazoles displayed a C-H stretching absorption in the 1214-1673 cm -1 range and a C-halogen stretching absorption in the 667-806 cm-1 range. The classical cycloaddition of phenylacetylene with benzyl azide without any catalyst, does not take place in toluene at room temperature, 19 or leads to a 1:1 mixture of regioisomers after a prolonged reaction time at reflux. 19 In addition, it is known that alkynes with an electronwithdrawing functional group favor the irreversible Huisgen cycloaddition reaction of azides and alkynes.…”
Section: Methodsmentioning
confidence: 99%
“…The classical cycloaddition of phenylacetylene with benzyl azide without any catalyst, does not take place in toluene at room temperature, 19 or leads to a 1:1 mixture of regioisomers after a prolonged reaction time at reflux. 19 In addition, it is known that alkynes with an electronwithdrawing functional group favor the irreversible Huisgen cycloaddition reaction of azides and alkynes. 20 It was also recently reported that it is possible to impart some regioselectivity into these thermal cycloaddition reactions by utilizing sterically or electronically biased alkynes.…”
Section: Methodsmentioning
confidence: 99%
“…Namely, MOF-99 (metal organic framework) (Nguyen et al 2012), polystyrene supported Cu(I)-imidazole complex (Li et al 2012), silica sulfuric acid (Wang et al 2009), phosphate-impregnated titania (Nath and Chaudhuri 2009), PSSA (polystyrenesulfonic acid) (Polshettiwar and Varma 2007), Amberlyst-15 (Das and Chowdhury 2007), MCM-41 (Mobil composition of matter) immobilized heteropoly acids (Xie et al 2013), HY zeolite (Jeganathan et al 2014), polystyrene-supported DABCO (1,4-diazabicyclo[2.2.2]octane), and TBD (1,5,4,0]dec-5-ene) (Sodhi et al 2015;Yu and Xu 2015), silica-bonded imidazolium-sulfonic acid chloride (SBISAC) (Moosavi-Zare et al 2015), zeolites (Chassaing et al 2007), polymers (Yamada et al 2012), non-magnetic and magnetic supported Cu(I) (Megia-Fernandez et al 2010), silica (Mnasri et al 2015), and TiO2-nanotube (Faraji et al 2016) all showed good catalytic activity. However, they do not completely fulfill the economic and sustainable protocols involved in the development of green processes.…”
Section: Introductionmentioning
confidence: 99%